China’s strategic thoughts and suggestions on promoting South Africa’s clean energy transition - Guo, Hongli; Feng, Wen; Yan, Ruining (Frontiers in Chemical Engineering, 2025)
This paper analyzes the structural challenges faced by South Africa, such as high dependence on coal power, low penetration rate of clean energy and lagging power grid infrastructure. Combined with the basis and bottlenecks of energy cooperation between China and South Africa, it proposes a multi-dimensional cooperation path centered on technological synergy, financial innovation and institutional adaptation. This path requires both sides to focus on joint research and development of clean energy technologies, cultivation of localized industrial chains and upgrading of smart grids. By innovating hybrid financing tools and risk hedging mechanisms, they can break through capital constraints and promote the reform of South Africa’s energy policy to activate market vitality. At the same time, it is emphasized to deeply integrate China’s advantages in the clean energy industry with South Africa’s resource endowments, establish a mutual recognition system for technical standards and a long-term mechanism for talent cultivation, and ultimately achieve the dual goals of optimizing South Africa’s energy structure and regionalizing the application of China’s technical standards. Clean energy cooperation between China and South Africa is not only about capacity matching, but also requires the establishment of a sustainable collaborative innovation ecosystem to provide a replicable regional cooperation model for the energy transition of emerging economies.